Pengaruh DPK, BOPO, Modal dan Net Imbalan terhadap Gross Profit Margin dan Pembayaran Bagi Hasil pada Bank Syariah di Indonesia - Sudirman, Sudirman; Febrianty Febrianty; Abdul Rahman (Al-Buhuts, 2025)
This research is based on indications that indicators can influence each other. For example, Third Party Funds can cause a decrease in Cost-to-Income Ratio, which can affect the bank's net profit. Likewise, increasing capital can cause an increase in bank net profit. The data analysis method used in this research is the path analysis method to see the relationship or influence of independent variables. On direct and indirect influences through intervening variables. The results of this research show that Third Party Funds does not have a significant influence on gross profit margin but does have a significant influence on profit-sharing payments. Cost-to-Income Ratio does not significantly impact gross profit margin but significantly impacts Profit Sharing Payments. Capital does not have a significant impact on gross profit margin but has a significant impact on Profit Sharing Payments. Net Rewards do not have a significant impact on gross profit margin but have a significant impact on Profit Sharing Payments. The findings of this research show that Third Party Funds, Cost-to-Income Ratio, Capital, and Net Returns do not influence Gross Profit Margin, but do influence Profit Sharing Payments in Sharia Banks in Indonesia